KIDding aside stigma and identity negotiation of childfree women in the workplace - Armamento, Denise E.; Catapal, Seine O.; Ilagan, Shanlee Ma. Edlor V.
Childfree women-those who choose not to have children-face significant stigma, especially with the traditional and gendered expectation of womanhood. Despite gaining autonomy over their lives, these women encounter backlash affecting their self-identity. While much research covers childfree women's general experiences, little focuses on their workplace experiences, especially since they spend most of their lives in career development. Hence, this study explores how childfree women navigate and negotiate their identities in the workplace. Through qualitative research using semi-structured interviews with six participants, the study found that childfree women define their identity around themes of freedom, lack of child-related responsibilities, and unfair workplace policies. They face stigmas such as unwarranted comments, teasing, unfair comparisons to mothers, and assumptions about having more time. To establish their identity, they use strategies classified as either self- confirmatory opportunities or selective interactions. The results of the study suggest that further research is needed to understand how workplace cultures and policies impact childfree women's identities.